The dissociation of the [a plus c] dislocation in GaN - Hirsch, P; Lozano, J; Rhode, S; Horton, M; Moram, M; Zhang, S; Kappers, M; Humphreys, C; Yasuhara, A; Okunishi, E; Nellist, P (2013)
In 1952, Cottrell proposed that the Lomer dislocation formed by interaction of two glide dislocations in a fcc crystal could transform into an immobile dislocation by dissociation into partial dislocations bounding a stacking fault, causing a block to further slip, a concept important in work hardening. Evidence for this and many other dissociations has been provided by the diffraction contrast technique and in particular by its 'weak beam' variant, which has a resolution limit of about 15 angstroms. Today, with the advent of aberration corrected microscopes it is possible to determine directly the atomic structure of the faults and partial dislocations. In this paper, we describe the results of a study using the High Angle Angular Dark Field technique (HAADF) in an aberration corrected scanning transmission electron microscope (STEM), of the dissociation of the [ a + c ] dislocations in (0 0 0 1) GaN films grown on sapphire substrates. The dislocations are found to be inclined with respect to the c-axis, but optical sectioning imaging methods allow the structure to be determined and an estimate of the tilt angle to be made. The dislocations are found to be dissociated by climb and glide on the a plane and the STEM results, and structural arguments supported by theoretical calculations suggest that the dissociation reaction is [ a + c ] = 1/2[ a + c ] + 1/2[ a + c ] + fault. The structure of the fault is found to be similar to that identified in 1965 by Drum in AlN but frequently modified by steps due to kinks in the inclined dislocation. © 2013 Copyright Taylor and Francis Group, LLC.